Beton Mutu Tinggi dengan Admixture Superplastisizer dan Aditif Silicafume - Pujianto, As’at (Jurnal Semesta Teknika, 2011)
Increasing concrete strength is one of the main necessities of concrete technology. For more than the last 20 years, high strength concretes with compressive strength ranging from 50 MPa up to 140 MPa have been used worldwide in high rise buildings and bridges with long spans, or buildings in aggressive environments. But in Indonesia high strength concretes possesses maximum compressive strength of 60 MPa. The properties of concrete are affected by cementitious matrix, aggregate, and the transition zone between these two phases. Reducing the water-cement ratio and the addition of pozzolanic admixtures like fly-ash are often used to modify the microstructure of the matrix and to optimise the transition zone. The reduction of the water-cement ratio results in a decrease in porosity and refinement of capillary pores in matrix, but flowing ability of the concrete will also decrease so that it canât be workable. Then it workablity can be improve by the use of a superplastisizer. The method used refers to the planning of normal concrete, which is contained in the SK-SNI 03-2834-1992. The results showed that superplastisizer with doses of more than 2% of the cement paste does not increase the flowing ability of the paste anymore. For all the rest of the experiments, the superplastisizer dosage was determined about 2 % of the powder mass. The first tests showed a good workability of the fresh concrete and a good self compacting ability with the silicafume dosage of 10 % of the powder mass. The interest in reducing costs for increasing the concrete strength, can be successfully achieved in this research.